Neuroplasticity and the microbiome: how microorganisms influence brain change - Al Noman, Abdullah; Alhudhaibi, Abdulrahman Mohammed; Afroza, Moushumi; Tonni, Susmita Deb; Shehab, Habibul Mohsin; Jahan Iba, Nusrat; Taha, Tarek H.; Abdallah, Emad M. (Frontiers in Microbiology, 2025)
Neuroplasticity, the brain's ability to reorganize and adapt, has traditionally been attributed to external stimuli, learning, and experience. However, emerging research highlights the gut microbiota as a key modulator of neuroplasticity through the gut-brain axis. This review examines the mechanisms by which intestinal microorganisms influence brain function, including microbial metabolite production, immune system modulation, neurotransmitter synthesis, and hormonal regulation. Dysbiosis, or microbial imbalance, has been linked to neurodevelopmental disorders, major depressive disorder (MDD), and cognitive impairments, emphasizing the microbiome's role in psychiatric and neurological health. Animal and human studies suggest that microbiota-targeted interventions, such as probiotics, prebiotics, and dietary modifications, may enhance neuroplasticity and mitigate mental health disorders. Future research should focus on understanding direct microbial-neuronal interactions and developing personalized microbiome-based therapies. This study underscores the gut microbiota's potential as a novel target for improving brain plasticity and mental health outcomes.